2017
DOI: 10.1152/ajpendo.00331.2016
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of PGC-1α increases peroxisomal activity and mitochondrial fatty acid oxidation in human primary myotubes

Abstract: Peroxisomes are indispensable organelles for lipid metabolism in humans, and their biogenesis has been assumed to be under regulation by peroxisome proliferator-activated receptors (PPARs). However, recent studies in hepatocytes suggest that the mitochondrial proliferator PGC-1α (peroxisome proliferator-activated receptor gamma coactivator-1α) also acts as an upstream transcriptional regulator for enhancing peroxisomal abundance and associated activity. It is unknown whether the regulatory mechanism(s) for enh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
60
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(65 citation statements)
references
References 58 publications
3
60
0
Order By: Relevance
“…Moreover, mitochondria and peroxisomes also share transcription factors for their biogenesis. The observed cooperative expressions of mitochondrial and peroxisomal proteins by PPAR activators (fibrates) or by over‐expression of PGC‐1 α further confirms the biogenetic link between mitochondria and peroxisomes. Therefore, for efficient protection against inflammatory damage to myelin and axons, functional and structural protection of mitochondria and peroxisomes and myelin/axons are important.…”
Section: Discussionsupporting
confidence: 55%
“…Moreover, mitochondria and peroxisomes also share transcription factors for their biogenesis. The observed cooperative expressions of mitochondrial and peroxisomal proteins by PPAR activators (fibrates) or by over‐expression of PGC‐1 α further confirms the biogenetic link between mitochondria and peroxisomes. Therefore, for efficient protection against inflammatory damage to myelin and axons, functional and structural protection of mitochondria and peroxisomes and myelin/axons are important.…”
Section: Discussionsupporting
confidence: 55%
“…In our in vitro system, we observed an inducing effect of EPO on genes previously known to play a role in myelination, such as Igf1, Igf2 , and Ptpre , as well as genes involved in lipid transport and metabolism, including Fat/Cd36, Ppargc1a/Pgc1alpha , and Pnlip ( 18 24 ).…”
Section: Discussionmentioning
confidence: 74%
“…To this purpose, we analyzed the changes in the gene expression profile induced by EPO in differentiating cells at two time points, 1 and 20 h after EPO treatment, focusing on the transcriptional changes occurring during the OPC to OL transition. The results highlight an inducing effect of EPO on genes previously known to play a role in myelination, such as insulin-like growth factor-1 ( Igf1 ), Igf2 , protein tyrosine phosphatase receptor type E ( Ptpre ), as well as genes involved in lipid transport and metabolism, including fatty acid translocase ( Fat/Cd36 ), peroxisome proliferator-activated receptor-gamma coactivator ( Ppargc1a / Pgc1alpha ), and pancreatic lipase ( Pnlip ) ( 18 24 ).…”
Section: Introductionmentioning
confidence: 97%
“…Nevertheless, genes encoding enzymes involved in peroxisomal FAO, but also mitochondrial FAO, were strongly suppressed in M1 microglia, indicating that a common transcriptional regulator might be involved. We hypothesize that peroxisome proliferator-activated receptor gamma coactivator (PGC)1α could be such regulator, as it has already been proven that PGC1α controls the expression of enzymes of both mitochondrial and peroxisomal βoxidation [78]. Moreover, it has also been shown that BV-2 microglia downregulate PGC1α expression upon LPS stimulation and that its overexpression leads to reduced inflammatory responses of microglia upon LPS stimulation, favoring PGC1α as a potential regulator of M1 polarization [79].…”
Section: Discussionmentioning
confidence: 97%